2009
DOI: 10.1523/jneurosci.4791-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Responses of Golgi Cells and Mossy Fibers to Eye Saccades and Saccadic Adaptation Recorded from the Posterior Vermis of the Cerebellum

Abstract: The anatomical organization of the granular layer of the cerebellum suggests an important function for Golgi cells (GC) in the pathway conveying mossy fiber (MF) afferents to Purkinje cells. Based on such anatomic observations, early proposals have attributed a role in "gain control" for GCs, a function disputed by recent investigations, which assert that GCs instead contribute to oscillatory mechanisms. However, conclusive physiological evidence based on studies of cerebellum-dependent behavior supporting/dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
87
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 32 publications
11
87
1
Order By: Relevance
“…Therefore, the high, very regular frequencies seen in granular layer recordings of the flocculus of the awake monkey (Miles et al, 1980) may not have reflected Golgi cells, but rather UB cells, whose extensive presence in the flocculus was not known at that time. Cells whose ISI histograms are like those of Golgi cells identified in the present study have been found in the vermis of the awake monkey (Prsa et al, 2009). Recent observations in slices showed that Golgi cells possess conductances enabling autorhythmicity.…”
Section: Golgi Cellssupporting
confidence: 79%
“…Therefore, the high, very regular frequencies seen in granular layer recordings of the flocculus of the awake monkey (Miles et al, 1980) may not have reflected Golgi cells, but rather UB cells, whose extensive presence in the flocculus was not known at that time. Cells whose ISI histograms are like those of Golgi cells identified in the present study have been found in the vermis of the awake monkey (Prsa et al, 2009). Recent observations in slices showed that Golgi cells possess conductances enabling autorhythmicity.…”
Section: Golgi Cellssupporting
confidence: 79%
“…A vertical organization of mossy-fiber input to the granular layer has recently been reported in the decerebrate cat (Jörntell and Ekerot 2006). Whereas in the latter study this resulted in modality-specific responses of granule cells, the present study and previous ones (Holtzman et al 2006;Prsa et al 2009;Vos et al 2000) indicate that GoCs integrate synaptic input from multiple receptive fields. A layered projection pattern could result from the layered distribution of attractants or repellants (Solowska et al 2002).…”
Section: The Sequence Of Synaptic Activations Probed With a 1d Electrsupporting
confidence: 64%
“…For the responses studied here, the broad activation (Fig. 10) implies a considerable convergence of mossy fibers onto GoCs and a loss of GoC selectivity (Prsa et al 2009). Whereas the lack of a trigeminal or putatively corticopontine peak in some GoCs, or equivalently in the same GoC at particular stimulus positions, may be explained as a selectivity in the mossy-fiber projection pattern, this would imply as well that the trigeminal and pontine projections are not perfectly aligned.…”
Section: Origins Of Response Variationmentioning
confidence: 82%
See 1 more Smart Citation
“…Although these speculations are intriguing because of the use of serotonergic and antiglutamatergic drugs in PBA, the function of various cells and neurotransmitters within the cerebellar microcircuitry, or their specific role in PBA, has not been clearly defined, and researchers continue their efforts to elucidate potential mechanisms within this circuitry and their potential role in cerebro-cerebellar loops [50][51][52][53].…”
Section: Cerebellar Mechanismsmentioning
confidence: 99%